Integration of musculoskeletal physical therapy care in the patient-centred medical home (IMPaC): protocol for a single-site randomised clinical trial. Issue 8 (8th August 2018) - Carvalho, Erik; Bettger, Janet P; Bowlby, Lynn; Carvalho, Marissa; Dore, Daniel; Corcoran, Misty W; Harris, Ashley A; Bond, Jennifer; Goode, Adam P
Abstract : Introduction: Annually, >50% of the US population reports musculoskeletal (MSK) pain to a provider, with direct healthcare costs exceeding $185 billion. The number of MSK complaints and the associated costs are projected to rise, increasing demand for and burden on providers. Establishing new care models to decrease inefficiencies may lower costs and optimise care delivery. The purpose of the Integration of Musculoskeletal Physical Therapy Care in the Patient-Centred Medical Home (IMPaC) study is to compare initial evaluation by a physical therapist (PT) integrated into primary care versus initial evaluation by a primary care provider (PCP) for patients with an MSK complaint. Methods and analysis: This single-site, randomised clinical trial will test the hypothesis that a PT within a primary care facility as the initial evaluating provider for patients with an MSK complaint will lower costs, improve utilisation (ie, reduced opioid prescriptions, imaging, physical therapy, emergency department visits and missed appointments) and increase patient satisfaction within 90 days of the index visit compared with PCP evaluation in the same location. Participants aged ≥18 years will be randomised with equal allocation and stratified by pain site (ie, back, knee, upper extremity and other). In the initial PT evaluation arm, patients will be assessed, treated and then instructed to complete a home exercise programme. The PCP cohort will undergo a usual PCP evaluation, and if a referral to physical therapy is made, patients will be randomised to onsite versus offsite physical therapy. Differences will be calculated and tested across the two arms. Ethics and dissemination: Approval was received from the Duke University Institutional Review Board (01 May 2017) and the National Institutes of Health, National Centre for Advancing Translational Sciences (01 January 2017). Findings will be communicated via quarterly reports to funding bodies and disseminated through scientific publications. Trial registration number: NCT03110211 ; Pre-results.